Service ecosystem boundary and boundary work - Razmdoost, Kamran; Alinaghian, Leila; Chandler, Jennifer D.; Mele, Cristina (Elsevier, 2022)
We aim to explain service ecosystem change at the intersection of focal service ecosystems through the concepts of boundary and boundary work. We define a service ecosystem boundary as a set of symbolic or social boundaries that enable the functioning of an ecosystem by identifying and authorizing actors and recognizing, legitimizing, and protecting resources. We further introduce boundary work and conceptualize the three types through which it manifests in service ecosystems: competitive, collaborative, and configurational. We further illustrate this typology by applying these types of boundary work in an analysis of the evolution of the music service ecosystem. Our paper has implications for the definition of actors and resources in service ecosystems in addition to the processes that include or exclude these actors and resources. Furthermore, our conceptualization contributes to the literature by providing a lens for investigating boundary changes in service ecosystems and explaining their fluidity or stability.
Keywords: Service-dominant logic; Service ecosystem; Institutional work; Boundary work; Institutional boundary; Service ecosystem change